Perfectionism and rational-emotive behaviour as a motivational policy for human resource management - Yu. A. Filyasova (Управление)
The article considers the concept of a perfectionist motivational policy, which promotes achieving a high level of intrinsic employee motivation that ensures accomplishment of the organisational duties maximum amount; meanwhile, additional compensation produces a motivation displacement eﬀect. Theoretically, perfectionism, as the organisation corporate culture value, contributes to a signiﬁcant resources saving for the personnel maintenance and development. Employees who ﬁnd themselves in a corporate perfectionist culture have the advantage of achieving a high autonomy level due to developing integrative abilities for regulating social actions. Perfectionist motivational policy is more typical for the company`s growth cyclical stage and more beneﬁcial for young people who have high goals regarding their professional development. Rational-emotive employees behaviour is a perfectionism operational correlate oriented towards catastrophic attitudes which stimulate continuous activity, maximum involvement in the organisation activities and the achievement of not only operational but also long-term company goals. Perfectionist motivational policy requires an independent employee performance appraisal, which limits the individuals’ personal inﬂuence on the organisation’s human resources policy. Inconsistency in implementation of the motivation structural elements not only hinders the motivation internalisation, but also provokes a rise in distrust of power structures in general due to the personnel management low culture in the organisation.